PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Amalia, Ratna (2015)
Penelitianinibertujuanuntukmengetahuigambarantentangpenerapanpendekatanpembelajaranmatematikarealistikuntukmeningkatkanpemahamankonsepmatematissiswadalammateripokokbangunruangsederhana di salahsatuSekolahDasarNegeriKecamatanSukasari Kota Bandung.Penelitianinidilatarbelakangikurangnyapemahamansiswadalammatapelajaranmatematikakhususnyapadamateribangunruangsederhana yang mengakibatkanberpengaruhterhadaphasilbelajarsiswakarenasiswabelumsepenuhnyapaham.Metode yang digunakandalampenelitianiniadalahPenelitianTindakanKelas (PTK) yang mengadaptasi model Kemmis& Mc. Taggart denganduasiklus. Penelitianinidilakukandenganduasiklus.Instrumen yang digunakandalampenelitianiniberupalembarevaluasitespemahamankonsepmatematis, observasi, catatanlapangan, wawancara, dandokumentasi.Analisis data dilakukandenganteknikkuantitatifdankualitatif. Data kuantitatifdiolahdengancaramencari rata-rata, sedangkan data kualitatifdiolahdengancaradeskriptif.HasilpenelitiandenganmenggunakanpendekatanPembelajaranMatematikaRealistik(PMR) padapembelajaranmatematikamenunjukkanadanyapeningkatan proses pembelajaran, terlihatpadakognitifsiswasaatmengerjakantesevaluasiberupalembarevaluasidenganpersentasesiklus I 69,44%denganskor rata-rata 70,28, dansiklus II mengalamipeningkatandenganmencapai94,44%denganskor rata-rata 81,94. Berdasarkanhasilpenelitian di atasdapatdisimpulkanbahwapenerapanpendekatanPembelajaranMatematikaRealistikdapatmeningkatkanpemahamankonsepmatematissiswapadamatapelajaranmatematikadenganmateripokokbangunruangsederhana This study aims to find an overview of the application of realistic mathematics learning approach to improve students' understanding of mathematical concepts in the subject matter of simple geometry in one State Elementary School Sukasarisubdistricts of Bandung. This research is motivated lack of understanding of students in the subjects of mathematics, especially in the wake of matter modest space resulting effect on student learning outcomes for students not yet fully understood. The method used in this research is a classroom action research (PTK) which adapt the model Kemmis& Mc. Taggart with two cycles. This research was conducted in two cycles. The instrument used in this study a comprehension test evaluation sheets mathematical concepts, observation, field notes, interviews, and documentation. Data analysis was performed with quantitative and qualitative techniques. Quantitative data is processed by finding the average, while the qualitative data is processed in a descriptive way. The results using the approach Realistic Mathematics Education (RME) in mathematics showed an increase in the learning process, look at the students' cognitive tests while working on an evaluation form evaluation sheet with the percentage of the first cycle of 69.44% with an average score of 70.28, and the cycle II increased to reach 94.44% with an average score of 81.94. Based on the above results it can be concluded that the application of Realistic Mathematics Education approach can enhance the students' understanding of mathematical concepts in mathematics with the subject matter of simple geometry.